The Effect of Educational Videos on the Level of Hypertension Knowledge at the Muara Bangkahulu Community Health Center, Bengkulu City - Amelia Cantika Hendri; Samwilson Slamet; Dwi Kurnia Putri; Tri Danang Kurniawan; Rizqa Hasanah (INDOGENIUS, 2026)
Background & Objective: Hypertension is a chronic disease that is a major risk factor for global mortality. This study aims to analyze the effect of providing educational videos on the level of knowledge of hypertensive patients about health management and medication adherence. Method: A quasi-experimental study with a pre- test and post-test design was conducted on 55 respondents at the Muara Bangkahulu Community Health Center, Bengkulu City, from January to March 2026. Data were collected using the Hypertension Knowledge-Level Scale (HK-LS) questionnaire consisting of 24 items. Result: Before the intervention, the majority of respondents were in the sufficient (69%) and poor (25%) knowledge categories, with an average score of 15.25. After the educational video was provided, there was a significant increase with the good category increasing to 27%, sufficient to 73%, and no more respondents in the poor (0%) category, with an average score increasing to 17.40. The Wilcoxon Signed Rank Test showed a p-value <0.001, indicating a very significant effect of education on increasing knowledge. A total of 53 respondents (96.4%) experienced an increase in knowledge after the intervention. Conclusion: In conclusion, educational videos have proven effective in improving the knowledge of hypertension patients, particularly regarding pharmacological adherence, healthy lifestyles, and understanding of disease complications. Recommendations include implementing ongoing education, using diverse media for different levels of education, and further research focusing on behavior change and long- term retention.